Characterizing lupus in African American children in Southern United States - Taylor B. Winstead; Spencer Hagwood; Cynthia Karlson; Anita Dhanrajani (Pediatric Rheumatology Online Journal)
Abstract Objective To characterize the clinical, demographic, and socioeconomic profile of childhood systemic lupus erythematous (cSLE) in the Black Belt of the Southern United States in comparison to the current literature of predominantly Caucasian cohorts. Methods This is a cross-sectional study characterizing patients with cSLE from two centers in the Southeastern United States– University of Mississippi Medical Center (UMMC) and University of Alabama at Birmingham (UAB). Demographic, social, and clinical data was retrospectively collected by medical chart review for prevalent and incident cSLE patients via electronic medical records for UMMC and the Childhood arthritis and rheumatology research alliance (CARRA) registry database for UAB. The data was combined and analyzed using SPSS statistical software. Results Of the 45 patients,82.2%were female, 82.2% were of AA ethnicity, and 66.7% had Medicaid insurance. Mean age at diagnosis was 13.5 years (+/- 2.8). Mean American College of Rheumatology (ACR) score at diagnosis was 5.1 (+/- 1.27), the Systemic Lupus International Collaborating Clinics (SLICC score) was 8.4 (+/- 2.5). Average baseline Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) was 13.06 (+/- 9.3), SLEDAI at 6 months and 1 year respectively was 7.4 and 4.7. Average distance traveled to see a rheumatologist was 74.83 miles compared to a national average of 42.8 miles. 37/45 patients (82%) belonged to medium-high or high Social Vulnerability Index (SVI) group based on zip code. Conclusion Compared to previously described multiethnic cohorts of cSLE, this predominantly AA patient population in the Southern United States has significantly higher disease activity and greater damage accrual. Social risk factors for this population include a higher SVI, longer distance from an academic pediatric rheumatology center, and having Medicaid insurance. The effect of these factors on disparity of disease outcomes needs to be further explored with larger cohorts.